Sexual harassment: a comparative study between Malaysia and United Kingdom / Nur Murni Zabiri ...[et al] - Zabiri, Nur Murni; Zakaria, Siti Noreane; Mohamed Rani, Zailisah; Mohd Salleh, Mohd Khuzaimi; Mansor, Hasib (2010)
The purpose of this research is to examine the possibility of enacting a specific law in Malaysia to which deals with sexual harassment. We have conducted a study to analyze the lacuna in our existing laws in handling cases related to sexual harassment by taking into consideration the application of the law in the United Kingdom with the aim of ascertaining the manner of redressing and remedying the victims of sexual harassment cases in Malaysia. Its objectives are to critically analyze whether the said existing laws would be adequate to resolve the sexual harassment cases and thereafter to also suggest and recommend civil remedies to sexual harassment victims through civil proceedings. To ena*ble us to obtain better understanding of the law on sexual harassment, we have employed qualitative methods whereby questions were designed and interviews were conducted. The overall results of the research showed that the effectiveness level of our existing laws in combating sexual harassment cases is less sufficient. Furthermore, the types of redress available to the victims of sexual harassment do not consist of any award for damages and compensation. Looking at the effects consequences of the sexual harassment upon the victims, we have made suggestions for the victims to be compensated with monetary remedy. The conclusion that we can draw from the research is that we do need to enact a specific law on sexual harassment in Malaysia in order to regulate sexual harassment at all places to enable fair and justice be delivered to the victims.